Isolation and Determination of the Major Chemical Compounds Present in Essential Oil of the Leaves of Myrtus Plant Grown in Khuzestan Province of Iran - Ashnagar, A.; Gharib Naseri, N.; Bayemani, A. (Asian Journal of Chemistry, 2010)
Myrtus plant has a variety of therapeutic properties. Regarding the abundance of the Myrtus plant grown around the city of Izeh, North East of Khuzestan province of Iran and its various therapeutic effects which have been used widely in the traditional medicine. The isolation of the main chemical components in the crude extracts obtained from the leaves of the myrtus shrub by maceration and Soxhlet extraction methods in various polar and non-polar solvents was carried out. The isolation and identification of the chemical components of the essential oil obtained by hydrodistillation from the leaves of Myrtus plant was done by using the advanced gas chromatography-mass spectrometry (GC-MS) technique. Maceration of the crushed leaves in toluene and Soxhlet extraction of the crushed leaves in toluene resulted in an oily material. TLC and column chromatography resulted in the separation of two fractions with Rf = 0.47 and 0.78. On the basis of various spectra (1H NMR, 13C NMR, UV-Visible, IR and MS), the fraction with Rf = 0.47 was identified as linalool (I) and the fraction with Rf = 0.78 was identified as 1,8-cineol (II). On the basis of the results obtained from GC-MS analysis of the volatile oil, it was concluded that the essential oil is consisted of four major components (α-pinene, 1,8-cineol, linalool and α-terpineol) totally 92.3 %, one minor component (linalyl acetate 1.1 %) and 23 other components with small amounts.